Morphological variation in the freshwater blenny Salaria fluviatilis from Corsican rivers: adaptive divergence, phenotypic plasticity or both?. Issue 1 (17th December 2013) - Magnan, P.; Proulx, R.; Berrebi, P.; Blondel, J.; Perret, P.; Roché, B.
<x xml:space="preserve">Abstract</x> The first goal of this study was to determine whether morphological variation in the freshwater blenny Salaria fluviatilis results in spatially structured populations distributed around Corsica, France, which would suggest genetically differentiated populations through reproductive isolation by distance. The second goal was to determine whether some morphological traits are related to water velocity, one of the most contrasting habitat characteristics in these rivers, which would suggest an adaptation to local conditions. The results showed that the morphology of S. fluviatilis differed among the three main geographic areas studied in Corsica and that geographically distant populations of S. fluviatilis were less similar morphologically and genetically than close ones. The results also indicated that the morphological differences among populations conformed to functional expectations. Overall, the results suggest that the morphological variation of S. fluviatilis from Corsican rivers is an adaptive response to water velocity and that these populations are in a process of reproductive isolation by distance.